The Heritability of Behaviors Associated With the Host Gut Microbiota - Manterola, Marcia; Palominos, M. Fernanda; Calixto, Andrea (Frontiers in Immunology, 2021)
What defines whether the interaction between environment and organism creates a genetic memory able to be transferred to subsequent generations? Bacteria and the products of their metabolism are the most ubiquitous biotic environments to which every living organism is exposed. Both microbiota and host establish a framework where environmental and genetic factors are integrated to produce adaptive life traits, some of which can be inherited. Thus, the interplay between host and microbe is a powerful model to study how phenotypic plasticity is inherited. Communication between host and microbe can occur through diverse molecules such as small RNAs (sRNAs) and the RNA interference machinery, which have emerged as mediators and carriers of heritable environmentally-induced responses. Notwithstanding, it is still unclear how the organism integrates sRNA signaling between different tissues to orchestrate a systemic bacterially-induced response that can be inherited. Here we discuss current evidence of heritability produced by the intestinal microbiota from several species. Neurons and gut are the sensing systems involved in transmitting changes through transcriptional and post-transcriptional modifications to the gonads. Germ cells express inflammatory receptors, and their development and function are regulated by host and bacterial metabolites and sRNAs thus suggesting that the dynamic interplay between host and microbe underlies the host’s capacity to transmit heritable behaviors. We discuss how the host detects changes in the microbiota that can modulate germ cells genomic functions. We also explore the nature of the interactions that leave permanent or long-term memory in the host and propose mechanisms by which the microbiota can regulate the development and epigenetic reprogramming of germ cells, thus influencing the inheritance of the host. We highlight the vast contribution of the bacterivore nematode C. elegans and its commensal and pathogenic bacteria to the understanding on how behavioral adaptations can be inter and transgenerational inherited.